2011 IEEE 35th Annual Computer Software and Applications Conference Workshops 2011
DOI: 10.1109/compsacw.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

IT Simply Works: Simplicity and Embedded Systems Design

Abstract: The central challenge in resource constrained systems is indeed that there is often a dramatic problem of resources: little memory, no display (i.e., mediated control and interaction), and weak processors. These constraints are due to various reasons, including cost (in economies of scale little amounts can make a big difference) and constraints mandated by the host environment such as limitations on weight, size, bandwidth, or power consumption. In addition to structural issues, that already force designers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In terms of the choice of models, we chose to combine simplicity [47] with formality [48,49], to enable ease of comprehension by a wide range of specialists and at the same time pave the way to automated verification and validation along the lines of [50] for model checking, [51] for automated synthesis, [49,52] for automated testing and validation, and [53] for the automated support of CI/CD. Altogether, the long-term goal is to support the full lifecycle of continuous model-driven engineering [54].…”
Section: Effects On Reusementioning
confidence: 99%
“…In terms of the choice of models, we chose to combine simplicity [47] with formality [48,49], to enable ease of comprehension by a wide range of specialists and at the same time pave the way to automated verification and validation along the lines of [50] for model checking, [51] for automated synthesis, [49,52] for automated testing and validation, and [53] for the automated support of CI/CD. Altogether, the long-term goal is to support the full lifecycle of continuous model-driven engineering [54].…”
Section: Effects On Reusementioning
confidence: 99%
“…In this paper, we revisit this concept from a simplicity perspective. By following the ITSy approach (Margaria, Floyd, & Steffen, 2011;Margaria & Steffen, 2010), it allows simpler usage, a higher level of abstraction, and usage of standards, while providing the ability to perform test cases which were previously not possible. As of now it allows to check the configuration in multiple ways without setting up a real network environment:…”
Section: Motivationmentioning
confidence: 99%
“…Margaria et al (2011); ) can be demonstrated eloquently with real-life examples readily being observable on the web. To be more specific, there are both examples of services that successfully adopt and maintain simplicity during their natural evolution and services that apparently are a lot less successful in this regard.…”
Section: Basics On Simplicitymentioning
confidence: 99%
“…The ITSy project (Margaria, Floyd, & Steffen, 2011; explores the power of simplicity in IT systems. To evaluate how the ITSy paradigm translates into real-life practice of IT systems development, concrete case studies have intrinsic and immediate value.…”
Section: Introductionmentioning
confidence: 99%